Animal model for immune dysfunction associated with adenosine deaminase deficiency. - Tedde, A (1980)
An in vivo murine model for immunodeficiency of both B and T cells is produced by continuous intraperitoneal infusion of 2'-deoxycoformycin (DCF), a specific tightly binding inhibitor of adenosine deaminase (ADase; adenosine aminohydrolase, EC 3.5.4.4). After DCF infusion, ADase of thymus, spleen, and lymph nodes was inhibited to varying degrees ranging from 57% to 100%. Immunodeficiency under these conditions was indicated by: (i) a striking decrease in lymphocyte response to the T-cell mitogens concanavalin A and phytohemagglutinin; (ii) an impairment of delayed hypersensitivity measured by the footpad reaction; (iii) a decrease in antibody production measured in both in vivo and in vitro plaque-forming cell assay; (iv) a significant prolongation of mouse skin allograft survival after transplantation into the C57BL/6J (H-2b) strain of skin from BALB/c (H-2d) mice; and (v) a marked lymphopenia. Histological examination indicated lymphoid degeneration in the thymus, lymph nodes, and spleen with no alterations in other tissues including bone marrow, kidney, lung, gastrointestinal tract, and liver except for the occurrence of hepatitis. A decrease in the number of Thy-1-positive cells in both spleen and lymph nodes further supported the fact of cytotoxicity of DCF to T cells. Anorexia and weight loss were observed within 5 days of continuous DCF infusion at 0.4 mg/kg body weight per day. These data indicate that this method provides an experimental model for future studies on the biochemical mechanisms responsible for the genetically determined severe combined immunodeficiency disease in man.